Community oral health literacy: improving use of oral-health care guarantee in children aged 6. - Marco Cornejo-Ovalle; Iris Delgado; Valentina Fajreldin; Ana González (Universidad de Concepción., 2013)
The assessment of comprehensive oral health care for children aged 6 (GES-6years) showed low utilization of this guarantee, with lower use for children from municipal public schools. The empowerment and health literacy of parents improve their role as oral-health promoters for their children. Objective: To implement and to assess a strategy of empowerment and health literacy of the community about their guaranteed health rights to increase the use of GES-6years. Methods: A mixed design. Using qualitative methodology we will design a communication tool, culturally and socially appropriate to be sent to the beneficiary community of this guarantee. Using a nonrandomized community trial, this instrument designed to empower and improve oral health literacy on GES-6 guarantee, will be sent as personalized letter (intervention) signed by the mayor of the municipality with a message aimed to children beneficiaries for GES -6years and another addressed to their parents/guardians. Schools would be selected from clusters (communes) of the two regions selected for convenience. Communes will be randomly selected amog those whose authorities agree to participate, and will be selected as for intervention or control. Data analysis will assess the differences in the prevalence of use of this guarantee among children from municipal schools belonging to the intervention or control arm.